Self-Compassion, Techno-eustress HUBUNGAN ANTARA SELF-COMPASSION DAN TECHNO-EUSTRESS PADA KARYAWAN YANG BEKERJA MENGGUNAKAN TEKNOLOGI - Gagan UNIBI (Psikologi UHAMKA, 2026)
The acceleration of digitalization requires employees who work with technology to continuously adapt, which may lead to cognitive and emotional strain. However, many employees perceive these demands as positive challenges that foster motivation and personal development. This study aims to examine the relationship between self-compassion and techno-eustress among employees who use technology in their work. The research employed a quantitative correlational method. The sample was selected using a purposive sampling technique, consisting of 324 employees who utilize technology in their daily work activities. The instruments used in this study were the Self-Compassion Scale and the Techno-Eustress Scale. Data were analyzed using Spearman’s rho correlation test. The results showed a significant relationship between self-compassion and techno-eustress, with a correlation coefficient of r = 0.223 and a significance value of p = 0.001 (p < 0.05). These findings indicate that the research hypothesis is accepted, meaning that there is a relationship between self-compassion and techno-eustress among employees who use technology in their daily work activities.